TMIC-45. DISTRIBUTION AND TUMOR CELL PROXIMITY OF IMMUNE CELLS IN THE TUMOR CORE, INFILTRATION ZONE AND PERIPHERY OF GLIOBLASTOMAS. (14th November 2022) - Pedersen, Vilde; Knudsen, Arnon Møldrup; Michaelsen, Signe Regner; Kristensen, Bjarne Winther
Abstract: Glioblastoma is the most frequent and malignant brain tumor. Immune therapies have had limited effect, but not much is known about the frequency and type of immune cells in the infiltration zone and periphery. In these areas, tumor cells migrate into the brain parenchyma and prevent total tumor resection thereby leading to recurrence. This study aims to quantify the type and distribution of immune cells in glioblastomas. A cohort of 67 glioblastomas was established containing tissue from central tumor and/or infiltration zone and/or tumor periphery. Patients were included if most tumor cells were positive in immunohistochemical staining for P53. A multiplex staining was established, where tissue sections were stained with P53 (tumor cells), FOXP3 (FOXP3+ regulatory T cells), CD8 (CD8+ cytotoxic T cells) and IBA1 (microglia/macrophages). Cells were counted in tumor core, infiltration zone and periphery using Visiopharm software based on training of convolutional neural networks. Moreover, the number of tumor cells with immune cells in proximity (30 µm) was quantified. The number of CD8+, FOXP3+ and Iba1+ cells was significantly higher in the core than in the periphery (P < 0.001), and in the infiltration zone than in the periphery (P < 0.001). However, the CD8+, FOXP3+ and Iba1+ cells/tumor cell ratio increased from core to infiltration zone and to periphery (P < 0.001). There was a higher amount of tumor cells with CD8+ cells in proximity in the tumor core (P < 0.001), whereas the highest amount of tumor cells with IBA1+ cells and FOXP3+ cells in proximity was the infiltration zone (P < 0.001). In conclusion, although levels of immune cells are highest in the tumor core - the higher proximity and ratio of immune cells to tumor cells in the infiltration zone/periphery suggest immune-suppressive mechanisms to be active in these areas.